Molecular interfacial properties and engineering performance of conductive fillers in cementitious composites - Sun, Junbo; Wang, Yufei; Li, K.; Yao, X.; Zhu, B.; Wang, J.; Dong, Q.; Wang, Xiangyu (ELSEVIER, 2022)
Conductive fillers, such as graphite particles (GP), steel slags (SS), and ground granulated blast furnace slag (GGBS) have been widely utilized in designing electrically conductive cementitious composites (ECCC) for various applications, including traffic detection, structural health monitoring (SHM), and pavement deicing. Owing to the complex working field, a comprehensive understanding of the role that the conductive fillers played in ECCC is essential for designing high-performance ECCC. In the present study, mechanical and conductivity experiments were conducted to explore the influences of these fillers on ECCC performances in strengths and electrical resistance. In addition, the reactive molecular dynamic (MD) simulation was firstly performed to quantify the interfacial properties of GP, SS, and GGBS in ECCC at the molecular level. Simulation results indicated that the chemical components of these conductive fillers dominate the atomic interfacial properties. Mineral components in SS or GGBS, especially Al2O3 and SiO2, led to a stronger interfacial bonding with cement in comparison to graphite in GP. At last, a hybrid mixing design of GP and SS was proposed in this study, balancing the mechanical and conductive performance of ECCC.